Preparation and Characterization of Ultra-Lightweight Foamed Concrete Incorporating Lightweight Aggregates - Mohamed Abd Elrahman; Mohamed E. El Madawy; Sang-Yeop Chung; Pawel Sikora; Dietmar Stephan (Applied Sciences, 2019)
Increasing interest is nowadays being paid to improving the thermal insulation of buildings in order to save energy and reduce ecological problems. Foamed concrete has unique characteristics and considerable potential as a promising material in construction applications. It is produced with a wide range of dry densities, between 600 and 1600 kg/m3. However, at a low density below 500 kg/m3, it tends to be unstable in its fresh state while exhibiting high drying shrinkage in its hardened state. In this study, lightweight aggregate-foamed concrete mixtures were prepared by the addition of preformed foam to a cement paste and aggregate. The focus of the research is the influence of fly ash, as well as fine lightweight aggregate addition, on the properties of foamed concrete with a density lower than 500 kg/m3. Concrete properties, including stability and consistency in the fresh state as well as thermal conductivity and mechanical properties in the hardened state, were evaluated in this study. Scanning electron microscopy (SEM) was used to study the microstructure of the foamed concrete. Several mixes with the same density were prepared and tested. The experimental results showed that under the same bulk density, incorporation of fine lightweight aggregate has a significant role on compressive strength development, depending on the characteristics of the lightweight aggregate. However, thermal conductivity is primarily related to the dry density of foamed concrete and only secondarily related to the aggregate content. In addition, the use of fine lightweight aggregate significantly reduces the drying shrinkage of foamed concrete. The results achieved in this work indicate the important role of lightweight aggregate on the stability of low-density foamed concrete, in both fresh and hardened states.